2019
DOI: 10.1016/j.jamcollsurg.2019.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Who Hurts More? A Multicenter Prospective Study of In-Hospital Opioid Use in Pediatric Trauma Patients in the Midwest

Abstract: BACKGROUND: Despite increased national attention on misuse of prescription and nonprescription opioids for adolescents and children, little is known about opioid use in a pediatric population during hospitalization for injury. The purpose of this investigation is to describe opioid administration and magnitude of opioid exposure in the first 48 hours of hospitalization in a pediatric trauma population. STUDY DESIGN: This is a secondary analysis of data collected for a randomized, prospective intervention study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…A recent review and meta-analysis by Zhang et al 18 found that current guidance for the prescription of opioids at DC after abdominopelvic surgery is heterogeneous and rarely supported by evidence. Pelaez et al 19 found that in a population of children, those with fractures required more opioids; they also noted that opioids were administered for a broad spectrum of injuries, including minor injuries. Bhashyam et al 20 also found that fracture location was an independent predictor of the amount of opioids prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review and meta-analysis by Zhang et al 18 found that current guidance for the prescription of opioids at DC after abdominopelvic surgery is heterogeneous and rarely supported by evidence. Pelaez et al 19 found that in a population of children, those with fractures required more opioids; they also noted that opioids were administered for a broad spectrum of injuries, including minor injuries. Bhashyam et al 20 also found that fracture location was an independent predictor of the amount of opioids prescribed.…”
Section: Discussionmentioning
confidence: 99%